Assessment of stability and plasticity of new hybrids of maize (Zea mays L.) under the conditions of Polissia and Steppe zones of Ukraine - Л. М. Присяжнюк; О. О. Шовгун; Л. В. Король; І. І. Коровко (Plant Varieties Studying and Protection, 2016)
Purpose. To select promising high productive maize hybrids of middle-early maturity group in terms of stability and plasticity of main economic characters. Methods. Field study, laboratory test, analytical procedure and statistical evaluation. Results. 14 maize hybrids recorded in the State Register of Plant Varieties Suitable for Dissemination in Ukraine in 2015 were studied for plasticity and stability of such traits as productivity, protein and starch content. Intensive highly-plastic hybrid ‘SI Tiptop’ was selected among the studied ones for productivity trait that can respond properly to changes of growing conditions. It was defined that for the starch content such hybrids as ‘SI Tiptop’, ‘SI Enigma’, ‘SI Arioso’, ‘Svich 38’, ‘Svich 35’, ‘HU 8653’, ‘Zdobutok’ and ‘SI Contrakt’ belonged to the intensive type and combined rather high values and the stability of the studied trait under variable conditions. The following hybrids as ‘NS 2642’, ‘DK S3016’, ‘Svich 38’, ‘NS 2632’ were qualified as intensive for protein content and appeared to be highly-plastic but stability values of this trait were low. ‘Svich 38’ hybrid was intensive simultaneously for two traits such as protein and starch content and showed rather high values of plasticity. ‘SI Tiptop’, ‘SI Enigma’ and ‘Svich 35’ were defined as hybrids of extensive type that provided stable protein content in adverse cultivation conditions. Conclusions. On the condition that intensive crop growing technologies should be used, for obtaining stable yields it is advisable to sow only highly-plastic hybrids that can adapt to unfavorable environmental factors, including ‘SI Tiptop’ – for productivity trait, ‘Zdobutok’ and ‘SI Kontrakt’ – for starch content, ‘MAC 24N‘, ‘NA 2642‘ and ‘Danubio’ – for protein content.